Human capital and public services performance in Bahrain: moderating effect of accountability and mediating effect of Islamic work ethics - Busenan, Ebrahim Farhan Mubarak Farhan (2018)
The main purpose of this study is to examine human capital and its relationship to public services performance, with accountability as a moderating variable and Islamic work ethics as a mediating variable, in the public sector of Bahrain. The motivation for this study is the inconsistent results as well as the lack of research in previous studies in this area. This study is underpinned by the resource-based view (RBV) theory and the contingency theory for the purpose of explaining the proposed conceptual framework. A total of 640 questionnaires were distributed to citizens of Bahrain via systematic random sampling in the four governorates of Bahrain and 384 questionnaires were returned, with 368 responses found usable. Pearson correlation analysis was used to analyze the direct relationship between human capital and public services performance. To identify the moderating impact of accountability on the relationship between human capital and public services performance, hierarchical regression analysis was used. At the same time, hierarchical regression analyses, i.e., Medgraph, the Sobel test and the Kock Mediation test, were used to identify the mediating impact of Islamic work ethics on the relationship between human capital and public services performance. The findings of this study evince that human capital has positive and significant relationships with public services performance. More importantly, this study confirms the mediating impact of Islamic work ethics on the relationship between human capital and public services performance. In addition, the findings of this study indicate no moderating impact of accountability on the relationship between human capital and public services performance. This study has some limitations and finally, makes some recommendations, contributions and suggestions for future researchers.